Changes in the genomes and methylomes of three Salmonella enterica serovars after long-term storage in ground black pepper - Davies, Cary P.; Jurkiw, Thomas; Haendiges, Julie; Reed, Elizabeth; Anderson, Nathan; Grasso-Kelley, Elizabeth; Hoffmann, Maria; Zheng, Jie (Frontiers in Microbiology, 2022)
Low moisture foods (LMFs) have traditionally been recognized as safe for consumption, as most bacteria require higher water content to grow. However, outbreaks due to LMF foods are increasing, and the microbial pathogen Salmonella enterica is frequently implicated. S. enterica can survive in LMFs for years, but few serovars have been studied, and the mechanisms which underlie this longevity are not well understood. Here, we determine that S. enterica serovars S. Tennessee, S. Anatum, and S. Reading but not S. Oranienburg can survive in the ground black pepper for six years. S. Reading was not previously associated with any LMF. Using both Illumina and Pacific Biosciences sequencing technologies, we also document changes in the genomes and methylomes of the surviving serovars over this six-year period. The three serovars acquired a small number of single nucleotide polymorphisms (SNPs) including seven substitutions (4 synonymous, two non-synonymous, one substitution in a non-coding region), and two insertion-deletions. Nine distinct N6-methyladenine (m6A) methylated motifs across the three serovars were identified including five which were previously known, Gm6ATC, CAGm6AG, BATGCm6AT, CRTm6AYN6CTC, and CCm6AN7TGAG, and four novel serovar-specific motifs, GRTm6AN8TTYG, GAm6ACN7GTA, GAA m6ACY, and CAAm6ANCC. Interestingly, the BATGCAT motif was incompletely methylated (35-64% sites across the genome methylated), suggesting a possible role in gene regulation. Furthermore, the number of methylated BATGCm6AT motifs increased after storage in ground black pepper for six years from 475 to 657 (S. Tennessee), 366 to 608 (S. Anatum), and 525 to 570 (S. Reading), thus warranting further study as an adaptive mechanism. This is the first long term assessment of genomic changes in S. enterica in a low moisture environment, and the first study to examine the methylome of any bacteria over a period of years, to our knowledge. These data contribute to our understanding of S. enterica survival in LMFs, and coupled with further studies, will provide the information necessary to design effective interventions which reduce S. enterica in LMFs and maintain a healthy, safe food supply.